Triamcinolone Injection Following Internal Urethrotomy for Treatment of Urethral Stricture - Tavakkoli Tabassi, Kamyar; Yarmohamadi, Aliasghar; Mohammadi, Shabnam (Urology Journal, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Purpose: To investigate the success rate of internal urethrotomy when combined with corticosteroid injection in urethral scar tissue for treatment of urethral stricture. Materials and Methods: We performed a double-blind, randomized, placebo-controlled study on 70 patients with urethral stricture, who underwent internal urethrotomy from June 2003 to July 2008. Patients were randomized into 2 groups; the experimental group (34 patients) who received triamcinolone acetonide injection and the control group (36 patients) that received an injection of sterile water after internal urethrotomy. Postoperative results were compared between two groups. Results: In the experimental group, 1 (2.94%), 3 (8.82%), and 2 (5.8%) patients developed infection, bleeding, and extravasation, respectively, and recurrence was noted in 12 patients. In the control group, infection, bleeding, and extravasation occurred in 2 (5.55%), 3 (8.33%), and 2 (5.55%) patients, respectively, and stricture recurred in 15 patients. There were no significant differences in stricture location as well as its etiology between the two groups (P = .672 and P = .936, respectively). Complication and recurrence rates in experimental group were lower than the control group, but the difference was not statistically significant (P = .847 and P = .584, respectively). However, time to recurrence decreased significantly in experimental group (8.08 ± 5.55 versus 3.6 ± 1.59 months) (P < .05). In our study, we did not find any complications that could be attributed to the triamcinolone acetonide injections. Conclusion: It seems that steroid injection after internal urethrotomy is a safe method, which may delay the recurrence of urethral stricture.